(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Haplophyllum Juss belongs to the family of sedges and is considered to be mainly perennial herbs and sometimes low-growing shrubs. The representatives of the genus are widespread in areas with sandy and loamy soft soil in the mountains and sub-mountain areas. It contains many biologically active substances and is widely used in medicine and various fields of folk medicine.